Targeting CRAC channels in inflammatory bowel disease - Sven Kappel; Christine Peinelt (EMBO Molecular Medicine, 2022)
Abstract Inflammatory bowel disease (IBD) is a collective term for inflammatory diseases of the human gastrointestinal (GI) tract that are characterized by perturbations in the intestinal immune responses. In their study, Letizia et al (2022) found an enrichment of CD4+ effector T cells, interferon gamma (IFNγ) producing CD8+ T cells, regulatory T cells, and innate lymphoid cells (ILC) in the lamina propria (LP) of IBD patients. In these cells, pharmacological inhibition of store‐operated calcium entry (SOCE) reduced cytokine production. In addition, in a murine IBD model, systemic SOCE inhibition reduced IBD severity and weight loss.